(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to know “the effect of the two strategies of collection and filtering of ideas on the reading comprehension of first-grade intermediate students.” The researcher followed the experimental research method and chose an experimental design with partial control. The researcher chose Division (B) to represent the first experimental group, which numbered (37) students, and Division (C) to represent the second experimental group, numbering (34) students, and Division (A) of the control group, which numbered (36) students. Research groups in a set of variables, the researcher prepared a test to measure reading comprehension that included (23) paragraphs that varied between (16) objective paragraphs of the type of multiple-choice and (7) essay paragraphs. The experiment continued for an entire semester of the academic year ( 2021-2022 AD), and the results resulted in the superiority of the two experimental groups over the control group in the reading comprehension test. The first intermediate class, by presenting the material in a different and distinctive way, and my strategy (aggregation and filtering of ideas) led to an increase in the acquisition of knowledge and knowledge of the smallest details of the topics. Similar to the current study in other stages of study, and conducting a similar study to the current study on females.